A Systematic Review of Teaching Games for Understanding Intervention Studies From a Practice-Referenced Perspective - Morales-Belando, María T.; Kirk, David; Arias-Estero, José L. (Research quarterly for exercise and sport, 2022)
According to the theory of practice architecture, every practice enacted in classrooms is a result of interaction between social, physical and spatial elements. In relation, from a practice-referenced perspective, it is necessary to know which teaching-learning implementation features could help teachers/coaches/researchers to assemble Teaching Games for Understanding (TGfU) interventions in relation to the institutional environment. Purpose: This review aimed to explore from a practice-referenced perspective how TGfU researchers reported their interventions based on the teaching-learning implementation features (intervention design as a function of the context, intervention length, lesson content, basic lesson elements, lesson alignment, teacher/coach experience with the approach, and lesson validation and treatment verification) and their association with learners' outcomes. Results: We found 20 studies that included some of the teaching-learning implementation features, but none of the studies included all of these features. We also found that studies of TGfU measured and reported learners' outcomes in a variety of ways. This creates difficulties for drawing conclusions about the relationships between the presence of teaching-learning implementation features and student learning outcomes. Conclusion: Further TGfU interventions should be planned to consider the following: (a) that lessons need to be designed as a function of the context; (b) the number of intervention lessons, their duration and the duration of each lesson task; (c) the concrete tactical and technique contents and goals per lesson; (d) the modified games, questions and achievable challenges as basic lesson elements; (e) the alignment between the basic lesson elements and the structure of lessons, based on the goals of each lesson; (f) that teachers/coaches need to have previous experience in TGfU and be trained on the specific study purpose; (g) that lessons should be validated before implementation and verified during intervention; (h) researchers should regulate the ways in which learners' outcomes are measured and reported within TGfU studies.